Древние оборонительные сооружения переправы через Дунай у озера Картал - Дзиговский, А.Н.; Сапожников, И.В. (Археологія і давня історія України, 2018)
В научный оборот вводятся выявленные на основании изучения топографических карт неизвестные ранее сооружения (валы и дороги), расположенные в указанном районе, а также оборонительный рубеж, состоящий из четырех линий полевых укреплений, обнаруженный в самой южной части водораздела между озерами Кагул и Ялпуг. The article is dedicated to the characteristics of the defense constructions in the area of river crossing of Danube near lake Kartal not far from village Orlovka of Reny district in Odessa region and their historical interpretation. The conclusion was made, that in this district in the first ages AD. the powerful defensive center functioned, created by Romans. In the center’s system there were Romans fortifications on the sites near the villages Orlovka and Novoselskoye altogether with the ramparts and graffs, which surrounded them, and also one more rampart, which was situated between those two fortificated points. The last one featured the rampart- road and was the important component of this defensive center. Romans started the creation of Kartal defensive center in the 60s years AD. and continued its organization during Vespasian’s regiment term. The center finished its functioning near the middle of the III century AD. As regards the fortificated area, situated between the left shore of lake Kagul and the right shore of lake Yalpug, according to the written sources’ information about the war events, which had taken place in Southern Budzhak in ancient times and considering the density of population of this part in the time of discussing events, we can suppose, the fortificated area may be built by Scythians in the last third of the IV century BC or by Goths in the last third of the IV century AD.